The Thrips formosanus group from Asia and Australia with a new species of the genus Thrips (Thysanoptera: Thripidae) from India - Tyagi, Kaomud; Kumar, Vikas (Zootaxa, 2015)
A new species-group in the genus Thrips is designated as Thrips formosanus group from Asia and Australia. This includes the following six species: T. floreus Kurosawa from Japan, T. formosanus Priesner from Taiwan, T. obscuripes Priesner and T. rostratus Priesner from Java, T. tanicus Bhatti from India and T. hoddlei Mound and Masumoto from Australia. One new species, Thrips moundi sp. n., is described in this group from specimens collected on grasses in Himachal Pradesh State of India. A key to the seven species of Thrips formosanus group is also provided. Partial sequence data for the gene mitochondrial cytochrome c oxidase (mtCOI) from the holotype and paratype of this new species is provided.